Efficient synthesis of azetidine-2,3-diones from L-(+)-diethyl tartrate - Chincholkar, Pinak M.; Puranik, Vedavati G.; Deshmukh, Abdul Rakeeb A. S. (Synlett, 2007)
A convenient route to enantiopure azetidine-2,3-diones is described. The chiral ketene generated from commercially available L-(+)-diethyl tartrate on Staudinger cycloaddition with different imines gave spiro-beta-lactams in good yields. These spiro-beta-lactams were transformed into azetidine-2,3-diones in excellent yields in a two-step process.
Keywords: Cycloaddition; imines; lactams; spiro compounds; stereoselective synthesis

Efficient formal synthesis of (S)-dapoxetine from enantiopure 3-hydroxy azetidin-2-one - Chincholkar, Pinak M.; Kale, Ajaykumar S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2009)
An efficient formal synthesis of S-(+) dapoxetine starting from 3-hydroxy azetidin-2-one is described. The intermediate (S)-3-(dimethyl amino)-3-phenylpropan-1-ol was synthesized in enantiopure form starting with 3-hydroxy azetidin-2-one in seven steps. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Azetidin 2 ones; beta-Lactams; Enantioselective synthesis; reduction; Staudinger reaction